The Challenge of Appropriate Identification and Treatment of Starvation, Sarcopenia, and Cachexia: A Survey of Australian Dietitians - Alison Yaxley; Michelle D. Miller (Journal of Nutrition and Metabolism)
Malnutrition is an umbrella term that includes starvation, sarcopenia, and cachexia; however, differentiating between these terms is infrequent in clinical practice. Given that the effectiveness of treatment depends on the aetiology of unintentional weight loss, it is important that clinicians are aware of the defining characteristics. The aim of this study was to determine whether Australian dietitians understand and use the terms starvation, sarcopenia, and cachexia and provide targeted treatment strategies accordingly. Members of the Dietitians Association of Australia were surveyed to gain information on practices and attitudes to diagnosis and treatment of adult malnutrition. In addition, three case studies were provided to examine understanding of starvation, sarcopenia, and cachexia. 221 dietitians accessed the survey. 81 respondents (43%) indicated the use of at least one alternate term (starvation, sarcopenia, and/or cachexia). Muscle wasting was the most commonly used diagnostic criterion. High-energy high-protein diet was the most common therapy prescribed. Correct diagnoses for case studies were recorded by 6% of respondents for starvation, 46% for sarcopenia, and 21% for cachexia. There is a need for increased awareness of the existence of starvation, sarcopenia, and cachexia amongst Australian dietitians and research into appropriate methods of identification and treatment for each condition.